Language by mouth and by hand - Iris Berent (Frontiers Research Topics, 2015)
While most natural languages rely on speech, humans can spontaneously generate comparable linguistic systems that utilize manual gestures. This collection of papers examines the interaction between natural language and its phonetic vessels - human speech or manual gestures. We seek to identify what linguistic aspects are invariant across signed and spoken languages, and determine how the choice of the phonetic vessel shapes language structure, its processing and its neural implementation. We welcome rigorous empirical studies from a wide variety of perspectives, ranging from behavioral studies to brain analyses, diverse ages (from infants to adults), and multiple languages - both conventional and emerging home signs and sign languages.